Metode Pengembangan Sumber Daya Manusia melalui Pendidikan dan Pelatihan di SMAN 1 Setu Kabupaten Bekasi - Irnie Victorynie; Lailatul Fitriah Eka Putri; Rosulinawati (Jurnal Dirosah Islamiyah, 2024)
The purpose of this study was to analyze the methods of human resource development applied at SMAN 1 Setu, and to identify the challenges and opportunities faced in its implementation. The research method used a descriptive qualitative approach. The results of the study showed that human resource development through education and training at SMAN 1 Setu, Bekasi Regency, had a positive impact on improving the quality of teaching and teacher competence. With various methods applied, such as competency-based training, utilization of technology, and collaboration between educators, SMAN 1 Setu succeeded in improving the professional skills of teachers in various aspects. The challenges of limited budget and time are still obstacles that need to be solved. Human resource development in schools will be more optimal if supported by various related parties.